Investigation on ablution (wudhuk) workstation design for wheelchair users in Malaysia / Nursyahirah Adnan - Nursyahirah, Adnan (2018)
Ablution (wuduk) is an important ritual of cleaning for Muslim that applies to every Muslim regardless of sex, age or physical status. So, this includes wheelchair users. However, the current design of ablution area in mosques around Malaysia do not provide proper accessibility for them. This is due to lack of standards and guidelines for designing the ablution workstation for them. Therefore, this study was conducted to propose an ergonomics design criteria of ablution workstation for wheelchair users especially in the mosques. A total 100 wheelchair users participated in the questionnaire to identify the comfort level, problems of existing ablution workstation and their suggestions for new ablution workstation. Moreover, the 15 anthropometry dimensions have been measured for 100 wheelchair users in Malaysia. Besides, the experiments using inclinometer which are related to posture when performing ablution have been conducted on 15 male and 8 female wheelchair users. The ergonomics design criteria of ablution workstation were listed based on their preferences and anthropometric dimension as well as the analysis results of RULA using CATIA software. The research findings have identified the important design criteria in designing ablution workstation for wheelchair users which are ergonomics shape of the sink, suitable water tap handle and flexible water tap to wash the feet. This study can be considered as preliminary study for the development of ergonomic ablution workstation design for wheelchair users.